Integrated morpho‐biochemical and transcriptome analyses reveal multidimensional response of upland cotton (Gossypium hirsutum L.) to low temperature stress during seedling establishment. Issue 6 (20th November 2021) - Kaur Dhaliwal, Lakhvir; Gannaban, Ritchel B.; Shrestha, Avinash; Shim, Junghyun; Kaur Mangat, Puneet; Singleton, Joshua J.; Angeles‐Shim, Rosalyn B.
Abstract: Cotton is a tropical/subtropical crop and is innately susceptible to cold. Using an approach that integrates morphological, biochemical, and transcriptome analyses, the study aimed to understand the molecular underpinnings of phenotypic adjustments in cotton seedlings under cold stress. Exposure of six cotton accessions to 15°C during the seedling stage significantly reduced chlorophyll content, stomatal conductance, plant height, and biomass, but increased malondialdehyde and proline production. Comparative transcriptome profiling of the cold‐sensitive accession SA 3781 grown under low and normal temperatures showed the upregulation of genes related to the production of reactive oxygen species (ROS) under cold stress. Despite a similar upregulation of genes encoding metabolites that can scavenge ROS and provide osmoprotection for the cell, the stressed plants still exhibited oxidative stress in terms of lipid peroxidation. This may be due in part to the upregulation of abscisic acid synthesis genes and downregulation of chlorophyll synthesis genes effecting lower stomatal conductance and chlorophyll contents, respectively. Additionally, stomatal closure which is required to avoid the cooling effect and dehydration under cold conditions may have contributed in reducing the net photosynthetic rates in plants exposed to low temperature. These findings provide an insight into the expression of key genes regulating the phenotypic changes observed in cotton in response to cold stress.